Unconventional oxygen reduction reaction mechanism and scaling relation on single-atom catalysts - Zhong, Lixiang (2022)
The electrochemical oxygen reduction reaction (ORR) mechanism was generally considered to be O₂→ OOH∗→ O∗→ OH∗→ H₂O (O∗ mechanism). This O∗ mechanism predicted reasonable ORR half-wave potential (E1/2) of Co/N/C but abnormally underestimated the one of Fe/N/C. Herein, we highlight an unconventional 2OH∗ ORR mechanism (O2→ OOH∗→ 2OH∗→ OH∗→ H2O), which was often ignored because the free energies (ΔG) of 2OH∗ and O∗ are equal, according to the famous scaling relation: 2ΔG(OH∗) = ΔG(O∗). This scaling relation is true for traditional catalysts with near-continuous active sites. We find a different scaling relation: ΔG(2OH∗) = ΔG(O∗) + 1.5 eV on single-atom catalysts (Me/N/C, Me = Fe, Co, etc.) and suggest that the 2OH∗ mechanism should not be overlooked. In consideration of both O∗ and 2OH∗ mechanisms, the ORR E₁/₂ values of Co/N/C and Fe/N/C are in good agreement with experimental results. This work reveals the structure dependence of ORR reaction mechanisms and scaling relations in single-atom catalysis, and it is also heuristic for other reactions, such as O₂ evolution and N₂ reduction on single-atom catalysts.